2020
DOI: 10.1021/acs.est.9b05332
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Primary and Secondary Particulate Brown Carbon in Two Chinese Cities of Xi’an and Hong Kong in Wintertime

Abstract: Brown carbon (BrC), an aerosol carbonaceous matter component, impacts atmospheric radiation and global climate because of its absorption in the near-ultraviolet−visible region. Simultaneous air sampling was conducted in two megacities of Xi'an (northern) and Hong Kong (southern) in China in winter of 2016−2017. The aim of this study is to determine and characterize the BrC compounds in collected filter samples. Characteristic absorption peaks corresponding to aromatic C−C stretching bands, organo-nitrates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 90 publications
6
42
0
Order By: Relevance
“…The ratio in GZ is lower than those in BB‐influenced areas, such as Beijing (58%) (Du et al., 2014), Atlanta (50%) (Hecobian et al., 2010), and Alabama (87%) (Washenfelder et al., 2015), but higher than that in a less‐polluted region of North Carolina (14%) (Xie, Chen, Holder, et al., 2019). Furthermore, we found that the contributions of secondary sources to total BrC absorption in Guangzhou (39%) was in the range measured in the wintertime of North China cities ( λ = 370 nm, 19%–48%), but much lower than those recorded on the Tibetan Plateau (70%) and Hong Kong (76%) (Wang, Han, et al., 2019; Wang, Ye, et al., 2019; Zhang et al., 2020), highlighting the dominant contribution of primary BrC in Guangzhou and the nonnegligible contributions from secondary BrC. Among secondary sources, NT is the most important source of secondary BrC, accounting for 16.4% of total BrC absorption.…”
Section: Resultsmentioning
confidence: 71%
“…The ratio in GZ is lower than those in BB‐influenced areas, such as Beijing (58%) (Du et al., 2014), Atlanta (50%) (Hecobian et al., 2010), and Alabama (87%) (Washenfelder et al., 2015), but higher than that in a less‐polluted region of North Carolina (14%) (Xie, Chen, Holder, et al., 2019). Furthermore, we found that the contributions of secondary sources to total BrC absorption in Guangzhou (39%) was in the range measured in the wintertime of North China cities ( λ = 370 nm, 19%–48%), but much lower than those recorded on the Tibetan Plateau (70%) and Hong Kong (76%) (Wang, Han, et al., 2019; Wang, Ye, et al., 2019; Zhang et al., 2020), highlighting the dominant contribution of primary BrC in Guangzhou and the nonnegligible contributions from secondary BrC. Among secondary sources, NT is the most important source of secondary BrC, accounting for 16.4% of total BrC absorption.…”
Section: Resultsmentioning
confidence: 71%
“…The ratio in GZ is lower than those in BB-influenced areas, such as Beijing (58%) (Du et al, 2014), Atlanta (50%) (Hecobian et al, 2010), and Alabama (87%) (Washenfelder et al, 2015), but higher than that in a less-polluted region of North Carolina (14%) . Furthermore, we found that the contributions of secondary sources to total BrC absorption in Guangzhou (39%) was in the range measured in the wintertime of North China cities (λ = 370 nm, 19%-48%), but much lower than those recorded on the Tibetan Plateau (70%) and Hong Kong (76%) (Wang, Han, et al, 2019;Zhang et al, 2020), highlighting the dominant contribution of primary BrC in Guangzhou and the nonnegligible contributions from secondary BrC. Among secondary sources, NT is the most important source of secondary BrC, accounting for 16.4% of total BrC absorption.…”
Section: Possible Source Contributions To Brc Adsorptionmentioning
confidence: 62%
“…The pyrolysis of lignin during biomass burning usually produces a variety of substituted phenols; subsequently, nitrophenol is generated through phenolic compounds with NO x . Overall, there were nine element formulae identified as nitroaromatic compounds, eight of which were also detected in Xie et al Five of the nitroaromatic compounds (including 4-nitrophenol, 4-nitrocatechol, 2-nitro-1-naphthol, 3-methyl-4-nitrocatechol and 2-methyl-4nitrophenol) usually come from biomass burning or are produced from the photo-oxidation of anthropogenic VOCs (e.g., toluene, benzene) under high-NO x in heavy traffic urban environments [58,59]. Moreover, C 10 H 17 NO 7 S (RT = 11.186 min) may be a nitroxy organic sulfate derived from monoterpenes, and C 8 H 18 O 4 S (RT = 13.446 min) detected in the sample may be an aliphatic organic sulfate [60].…”
Section: Analysis Of Brown Carbon Chromophoresmentioning
confidence: 85%